The Impact of Tax, Product and Labour Market Distortions on the Phillips Curve and the Natural Rate of Unemployment - Nikola Bokan; Andrew Hughes Hallett (Kiel Institute for the World Economy (IfW), 2007)
Most people accept that structural and labour market reforms are needed in Europe. However few have been undertaken. The usual conjecture is that reforms are costly in economic performance and costly to finance. Blanchard and Giavazzi (2003) and Spector (2004) develop a general equilibrium model with imperfect competition to show the impact of labour or product market deregulation. We extend that model to combine both reforms, and include the costs of financing them, the conflict between long run gains and short run costs, and to allow for reforms of distortionary taxation. We also extend the model to explain the natural rate of unemployment and non-wage employment costs, to show the impact of reform on the short and long run Phillips curve parameters. We find that structural reforms imply short run costs but long run gains (unemployment rises and then falls, while wages move in the opposite way); that the long run gains outweigh the short run costs; and that the financing of such reforms is the main stumbling block. We also find that the implications for welfare improvements and employment generation are quite different: tax reforms are more effective for welfare, but market liberalisation for employment.
Keywords: E24; H23; J58; 330; Structural reform; wage bargains; short vs. long run substitutability; endogenous entry of firms; Phillips-Kurve; Natürliche Arbeitslosigkeit; Deregulierung; Arbeitsmarktflexibilisierung; Steuerwirkung; Allgemeines Gleichgewicht; Unvollkommener Wettbewerb; Beschäftigungseffekt; Wohlfahrtseffekt; Theorie